Review on The Compatibility of Fusion Reactor Structural Materials with High-temperature Liquid Metals. (September 2020) - Si, Cong; Lu, Wei; Ji, Junyu; Zhang, Shufeng; Yao, Xiangyang; Wang, Weihua; Chu, Delin
Abstract: This paper aims at the current candidate structure materials for fusion reactors such as RAFM (Reduced Activated Ferritic / Martensitic) steel, SiCf / SiC composites and V alloy, summarizing and analyzing the research progress of their corrosion compatibility in the liquid metal Li and LiPb, which includes static corrosion and dynamic corrosion research such as circuit corrosion and rotary corrosion. The review in this paper hopes to provide a reference for corrosion compatibility for the development of fusion reactor structural materials.